A game theoretic model of cooperation and non-cooperation for soccer playing robots - Bader-El-Den, Mohamed; Badreddin, Essameddin (IFAC Proceedings Volumes, 2016)
This paper proposes a model which combines cooperative and non-cooperative behaviors among autonomous mobile robots. This problem is well demonstrated by the Soccer playing robots, which consists of two sub-games, namely a non-cooperative game between the teams, and a cooperative game among the players of the same team. Game theory is used for modeling these games. The model consists of two layers, the first for the non-cooperative game which feeds its output to the cooperative game in the second layer. Fuzzy logic is used to evaluate the utility functional. The model is implemented using a soccer playing robot simulator.